2019
DOI: 10.1002/med.21638
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of small molecule HIV‐1 latency reversing agents identified in low‐ and high‐throughput small molecule screens

Abstract: The latency phenomenon produced by human immunodeficiency virus (HIV-1) prevents viral clearance by current therapies, and consequently development of a cure for HIV-1 disease represents a formidable challenge. Research over the past decade has resulted in identification of small molecules that are capable of exposing HIV-1 latent reservoirs, by reactivation of viral transcription, which is intended to render these infected cells sensitive to elimination by immune defense recognition or apoptosis. Molecules wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 193 publications
(254 reference statements)
6
31
0
Order By: Relevance
“…This strategy is known as shock-and-kill ( Figure 2 ) [ 83 , 84 , 85 ]. As of today, more than 300 molecules have been evaluated in vitro to reactivate latent HIV-1, including epigenetic, chromatin, signaling, and transcription modulators [ 86 , 87 ]. The chromatin-modifying agents, HDAC inhibitors (e.g., Vorinostat, Romidepsin and Panobinostat), are the most characterized class of LRAs explored in shock-and-kill approaches [ 86 ].…”
Section: Latency Reversal Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy is known as shock-and-kill ( Figure 2 ) [ 83 , 84 , 85 ]. As of today, more than 300 molecules have been evaluated in vitro to reactivate latent HIV-1, including epigenetic, chromatin, signaling, and transcription modulators [ 86 , 87 ]. The chromatin-modifying agents, HDAC inhibitors (e.g., Vorinostat, Romidepsin and Panobinostat), are the most characterized class of LRAs explored in shock-and-kill approaches [ 86 ].…”
Section: Latency Reversal Agentsmentioning
confidence: 99%
“…As of today, more than 300 molecules have been evaluated in vitro to reactivate latent HIV-1, including epigenetic, chromatin, signaling, and transcription modulators [ 86 , 87 ]. The chromatin-modifying agents, HDAC inhibitors (e.g., Vorinostat, Romidepsin and Panobinostat), are the most characterized class of LRAs explored in shock-and-kill approaches [ 86 ]. Three clinical trials using vorinostat clearly demonstrated an increase in HIV-1 RNA in resting CD4 + T cells; however, this was insufficient for robust protein production and did not have a meaningful impact on the size of the HIV-1 reservoir [ 88 , 89 , 90 ].…”
Section: Latency Reversal Agentsmentioning
confidence: 99%
“…To date, numerous LRAs have been reported to act through two major cellular pathways: PKC activation and HDAC inhibition (10,11). To determine whether KA and anthralin function as PKC activators, we asked if their activities in live J-Lat 9.2 cells were antagonized by the pan-PKC inhibitor GÖ-6983 (27).…”
Section: Ka and Anthralin Do Not Function As Pkc Activators Or Hdac Imentioning
confidence: 99%
“…Numerous LRAs have been described representing different functional classes. The majority represents protein kinase C (PKC) activators and histone deacetylase (HDAC) inhibitors, although agents that act by other mechanisms such as BET bromodomain and DNA methyltransferase inhibition are also intensively studied (10,11). However, LRAs tested to date in humans have shown limited clinical success due to extensive toxicity, poor efficacy, inconsistent viral reactivation, and/or insufficient engagement of cellular "kill" mechanisms (10,12).…”
mentioning
confidence: 99%
“…The "kill" involves the immune system's ability to recognize and clear cells that express viral antigens. A number of small molecules have been identified that function as latency reversal agents (LRAs) in CD4 + T cell lines and patient cells ex vivo [reviewed in [10][11][12]]. One class of LRAs are PKC agonists which function through activation of NF-B and the subsequent stimulation of RNAP II transcription via the NF-κB sites in the viral long terminal repeat (LTR) sequences.…”
Section: Introductionmentioning
confidence: 99%